2015
DOI: 10.1007/s12576-015-0365-8
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of apoptosis in myocardial reperfusion injury and loss of cardioprotection in diabetes mellitus

Abstract: Ischemic heart disease is one of the major causes of death worldwide. Ischemia is a condition in which blood flow of the myocardium declines, leading to cardiomyocyte death. However, reperfusion of ischemic regions decreases the rate of mortality, but it can also cause later complications. In a clinical setting, ischemic heart disease is always coincident with other co-morbidities such as diabetes. The risk of heart disease increases 2-3 times in diabetic patients. Apoptosis is considered to be one of the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 109 publications
3
39
0
Order By: Relevance
“…It has been reported that an increase in Bcl-2 expression decreases the rate of ATP consumption during ischemia and reduces IR-induced apoptosis, which during IR injury can cause cardiac dysfunction; prevention of apoptosis could be considered as a new aim for cardioprotection against IR injury (Badalzadeh et al, 2015). It has been previously shown that IPost showed an antiapoptotic effect on the heart (Xing et al, 2008), a finding observed in our control group as well.…”
Section: Discussionsupporting
confidence: 79%
“…It has been reported that an increase in Bcl-2 expression decreases the rate of ATP consumption during ischemia and reduces IR-induced apoptosis, which during IR injury can cause cardiac dysfunction; prevention of apoptosis could be considered as a new aim for cardioprotection against IR injury (Badalzadeh et al, 2015). It has been previously shown that IPost showed an antiapoptotic effect on the heart (Xing et al, 2008), a finding observed in our control group as well.…”
Section: Discussionsupporting
confidence: 79%
“…[23] Administration of troxerutin has reversed the excitotoxic brain damage and improved memory and cognitive impairment in the hippocampus of nondiabetic mice[13] and enhanced the spatial learning in rats. [20] However, the underlying mechanisms of these protective actions of troxerutin have not been yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…These include impaired kinase and signalling pathways. Specifically, these are altered extracellular signal-regulated kinase (ERK) 1/2 [116, 117], decreased phosphorylation of glycogen synthase kinase-3 beta [117, 118], impaired [112, 113, 117] or chronic [114] Akt phosphorylation and Akt activity [119], effects on mitochondrial adenosine triphosphate (ATP)-dependent potassium channels [106, 120124], decreased CGRP [125], reduced adenosine [108], altered bioavailability of NO [126] and abnormalities of other apoptotic pathways [127, 128]. In a human RIPC diabetes study, raised O -linked β- N -acetylglucosamine was found to be associated with a state of chronic cardioprotection, with subsequent RIPC providing no additional benefit [129].…”
Section: Difficulties In Clinical Translation Of Ischaemic Conditionimentioning
confidence: 99%